A Phase I/II Placebo-Controlled Trial of C1-Inhibitor for Prevention of Antibody-Mediated Rejection in HLA Sensitized Patients. Issue 2 (February 2015) - Vo, Ashley A.; Zeevi, Adriana; Choi, Jua; Cisneros, Kristen; Toyoda, Mieko; Kahwaji, Joseph; Peng, Alice; Villicana, Rafael; Puliyanda, Dechu; Reinsmoen, Nancy; Haas, Mark; Jordan, Stanley C.
Abstract : Background: Antibody-mediated rejection (AMR) is a severe form of rejection, mediated primarily by antibody-dependent complement (C) activation. C1 inhibitor (C1-INH, Berinert) inhibits the classical and lectin pathways of C activation. We performed a randomized, placebo-controlled study using C1-INH in highly sensitized renal transplant recipients for prevention of AMR. Methods: Twenty highly sensitized patients desensitized with IVIG + rituximab ± plasma exchange were enrolled and randomized 1:1 to receive plasma-derived human C1-INH (20 IU/kg/dose) versus placebo intraoperatively, then twice weekly for 7 doses. Renal function, adverse events (AEs)/serious AEs, C3, C4, and C1-INH levels were monitored and C1q+ HLA antibodies were also blindly assessed. Results: One patient in the C1-INH group versus 2 patients in the placebo group developed serious AEs, but none were related to study drug. Delayed graft function developed in 1 C1-INH subject and 4 in the placebo. The C1-INH trough levels increased with C1-INH treatment. C3 and C4 levels also increased significantly in the C1-INH group compared to placebo. No C1-INH patient developed AMR during the study. Two patients developed AMR after the study. Three placebo patients developed AMR, one during the study. C1q+ donor specific antibodies were reduced in 2 C1-INH treated patients tested, while immunoglobulin G DSA levels showed decreased binding for both groups. Conclusions: The C1-INH appears safe in the posttransplant period. The C1-INH treatment may reduce ischemia-reperfusion injury. The C1-INH also resulted in significant elevations of C1-INH levels, C3, C4, and reduced C1q+ HLA antibodies. Taken together, the combination of antibody reduction and C1-INH may prove useful in prevention of AMR. Further controlled studies are warranted. Abstract : A double-blinded phase II study of complement inhibition for prevention of antibody-medicated rejection has demonstrated promising safety and efficacy data.